85. Digital acuity measured by "the bumps" device correlates with degeneration of digital mechanoreceptors in peripheral neuropathies. Issue 12 (December 2017) - Provitera, V.; Stancanelli, A.; Caporaso, G.; Saltalamacchia, A.; Borreca, I.; Lanzillo, B.; Wendelshafer-Crabb, G.; Santoro, L.; Kennedy, W.R.; Nolano, M.
Abstract : "The bumps" is a sensitive test to quantify tactile threshold of fingerpads. We tested its ability to detect distal axonal degeneration in peripheral neuropathies. The bumps device is a checkerboard-like surface divided into squares. Each square includes 5 colored circles, one of which contains a round bump (height range 2.5–14  μ m) to identify using the fingerpad. For each subject, we defined the height of the lowest bump such that it and the next 2 highest were detected. Functional data were compared to the density of Meissner corpuscles (MC) in fingertip skin biopsies processed and quantified according to standard procedures. Study population included 86 subjects (M/F = 51/35; age = 52.3 ± 15.1) affected by peripheral neuropathy and 15 subjects (M/F = 9/6; age = 50.4 ± 13.9) affected by CNS pathology as control group. Average threshold in the neuropathy group was 7.0 ± 4.4  μ m, average MC density was 9.3 ± 7.3/mm 2 . Average threshold in the CNS pathology group was 7.4 ± 5.1  μ m and average density of MC was 10.5 ± 6.8/mm 2 . Digital acuity threshold correlated with the density of Meissner corpuscles in the neuropathy group ( r  = 0.353; p  < 0.01), but not in the CNS pathology group ( r  = 0.048; p  = 0.865). The Bumps is a sensitive and easy-to-use tool, suitable to detect degeneration of sensory endings in peripheral neuropathies.